2016
DOI: 10.1093/femsec/fiw190
|View full text |Cite
|
Sign up to set email alerts
|

Interspecific metabolic diversity of root-colonizing endophytic fungi revealed by enzyme activity tests

Abstract: Although dark septate endophytes (DSE) represent a worldwide dispersed form group of root-colonizing endophytic fungi, our knowledge on their role in ecosystem functioning is far limited. In this study, we aimed to test if functional diversity exists among DSE fungi representing different lineages of root endophytic fungal community of semiarid sandy grasslands. To address this question and to gain general information on function of DSE fungi, we adopted api-ZYM and BioLog FF assays to study those non-sporulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 60 publications
6
34
0
Order By: Relevance
“…Both DSE species used in our experiments were able to grow in vitro on different media with organic and inorganic sources of N and P. This indicates the enzymatic capabilities of these DSEs to degrade and utilise complex forms of N and P, which agrees with previous findings about different DSE species suggesting their potential to help plants via the mobilisation of nutrients from organic sources (Caldwell et al 2000). Mandyam et al (2010) have also shown that DSEs, including different isolates of P. macrospinosa, are able to utilise both organic and inorganic sources of N. Knapp and Kovács (2016), using enzyme assays, have shown that different DSE fungi, including P. macrospinosa and Cadophora sp., have a broad range of enzymes and can use a wide range of carbon and other sources of nutrients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Both DSE species used in our experiments were able to grow in vitro on different media with organic and inorganic sources of N and P. This indicates the enzymatic capabilities of these DSEs to degrade and utilise complex forms of N and P, which agrees with previous findings about different DSE species suggesting their potential to help plants via the mobilisation of nutrients from organic sources (Caldwell et al 2000). Mandyam et al (2010) have also shown that DSEs, including different isolates of P. macrospinosa, are able to utilise both organic and inorganic sources of N. Knapp and Kovács (2016), using enzyme assays, have shown that different DSE fungi, including P. macrospinosa and Cadophora sp., have a broad range of enzymes and can use a wide range of carbon and other sources of nutrients.…”
Section: Discussionsupporting
confidence: 90%
“…seemed to more efficiently use inorganic N and P than organic N and P. However, Cadophora sp. have showed a more diverse and stronger enzyme degrading capacity than P. macrospinosa when the enzyme capacities of these DSEs were tested using different enzyme assays (Knapp and Kovács 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…AMF protect plants from pathogens (Sikes et al, 2009), help plants cope with drought stress (Aug e, 2001), and aid plants in the uptake of phosphorus (P) and nitrogen (N) (Johnson et al, 2010). DSE are facultative fungal symbionts that can live on organic debris and in biological soil crusts in addition to plant roots (Menkis et al, 2004;Green et al, 2008;Day and Currah, 2011), and several studies have reported enzymatic activities by DSE capable of degrading organic matter (Mandyam and Jumpponen, 2005;Mandyam et al, 2010;Knapp and Kov acs, 2016). They are a polyphyletic group with members typically found in the phylum Ascomycota and are characterized by their dark, melanized, septate hyphae (Jumpponen and Trappe, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…In this connection, other studies demonstrated that Phialocephala fortinii can hydrolyze carboxymethylcellulose (12, 13) and colonize the tracheids of softwoods (14). In addition, it has been shown that other root-and foliage-associated DSEs will utilize a wide spectrum of substrates (15, 16). Thus, latent saprotrophy may be widespread among DSEs including, at least in the initial stages, the decomposition of forest litter (47), twigs (48, 49) and logs (50).…”
Section: Resultsmentioning
confidence: 99%